OPTIMIZING SALES THROUGH DIGITAL MARKETING IN MSMES IN WEST JAVA - Yuliafitri, Indri; Mulyani, Sri (LPPM Univ. Ibn Khaldun Bogor, 2024)
Community service o gather is one of the Tri Dharma of higher education. This service was carried out for two months during the Covid-19 pandemic, so there is a limited access to gather offline. Therefore, under the supervision of lecturers, students provide assistance to MSMEs around their homes in the West Java region. The peak activity of this service is a webinar on optimizing marketing using social media. The program carried out in this service is helping partners to increase market share and sales through digital marketing, especially social media such as WhatsApp, Facebook, and Instagram. In addition, partners are also assisted to be able to open a shop on an existing marketplace. Partners who sell food are helped to become Gofood and/or GrabFood partners. Partners are also given knowledge about running a business through the marketplace, so that their business can grow more. The end of result of this service is that partners can increase their market share and sales.